Da tinta ao sangue: o ensino de idade média a partir de Game of Thrones - Rampazzo, Henrique Bondan (My University, 2022)
The present work discusses the use of the fantasy gender in History teaching. Movies and series with medieval ambiance have increasingly permeated modern worldwide popular culture; great successes of box office and critic, they, however, attract crowds that presume several of the more realist aspects of these works as veridical, despite obvious fantastical elements. The lack of analysis of said verisimilitudes constantly damages historical knowledge, therefore, this essay proposes the utilization of said medias to help understand between the authors' poetical liberties and medieval knowledge, seeking yet to promote the didactization and utilization of the culture of the students in class. In order to achieve such ends, this work analyses the series Game of Thrones, from George R.R. Martin, based on the original book saga, The Chronicles of Ice and Fire, from an approach that highlights the importance of the utilized work, and of fantasy overall, as well as a brief history of the fantastical literary gender and its adaptation to seriated media. Employing this methodology, it was possible to comprehend the possibility of historical analysis of fantasy through its relations of verisimilitude with the medieval context, as well as its advantages in the classroom concerning the utilization of the students' culture in teaching, besides offering the teacher a support material in the form of video lessons created as an example of application of the discussed theme in the school; these video lessons are present in the YouTube channel "Da Tinta ao Sangue". [resumo fornecido pelo autor]
No presente trabalho, discute-se o uso do gênero da fantasia no ensino de História. Filmes e seriados com ambientação medieval permeiam cada vez mais a cultura popular do mundo contemporâneo; grandes sucessos de bilheteria e crítica, eles atraem multidões que, contudo, tomam muitos dos aspectos mais realistas dessas obras como verídicos, apesar de elementos obviamente fantásticos. A falta de análise acerca de tais verossimilhanças prejudica constantemente o conhecimento histórico. Portanto, propõe-se, na presente dissertação, a utilização dessas mídias para auxiliar na compreensão entre as liberdades poéticas tomadas pelos autores e o conhecimento medieval, almejando, ainda, promover a didatização e utilização da cultura dos alunos em sala de aula. Para alcançar tais fins, o trabalho analisa o seriado Game of Thrones, de George R.R. Martin, baseado na saga original de livros, As Crônicas de Gelo e Fogo, a partir de uma abordagem que destaca a importância da obra utilizada, e da fantasia de forma geral, bem como uma breve história do gênero literário fantástico e de sua adaptação para a mídia seriada. Empregando essa metodologia, foi possível compreender a possibilidade de análise histórica da fantasia através de suas relações de verossimilhança com o contexto medieval, bem como suas vantagens para a sala de aula concernentes na utilização do cotidiano dos estudantes na didática, além de oferecer ao professor um material de apoio na forma de videoaulas confeccionadas como exemplo de aplicação do tema discutido na escola; videoaulas essas presentes no canal do YouTube "Da Tinta ao Sangue". [resumo fornecido pelo autor]
Keywords: História - Estudo e ensino; Idade Média - História; Game of thrones (Programa de Televisão); Ensino audiovisual; Fantasia - Educação; History - Study and teaching; Middle ages - History; Game of Thrones (Television program); Audio-visual education; Fantasy - Education